2009
DOI: 10.1158/0008-5472.can-08-4147
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RhoB Expression Promotes Migration and Invasion of Human Bronchial Cells Via Activation of AKT1

Abstract: Lung cancer is the leading cause of cancer-related death worldwide, mainly due to its highly metastatic properties. Previously, we reported an inverse correlation between RhoB expression and the progression of the lung cancer, occurring between preinvasive and invasive tumors. Herein, we mimicked the loss of RhoB observed throughout lung oncogenesis with RNA interference in nontumoral bronchial cell lines and analyzed the consequences on both cell transformation and invasion. Down-regulation of RhoB did not mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 35 publications
11
83
1
Order By: Relevance
“…Moreover, RhoB loss could induce Rac1-dependent mesenchymal cell invasion in lung cells through the control of PP2A activity, 29 and promote the invasion of human bronchial cells via the activation of AKT1. 42 Furthermore, Mazieres et al 43 also reported that the loss of RhoB expression was induced via epigenetic regulation by histone deacetylation in lung cancer, whereas we found that LSD1 recruited by DUXAP8-mediated histone demethylation also contributed to RHOB loss of expression in NSCLC cells. Interestingly, rescue experiments demonstrated that the pseudogene DUXAP8 exerts oncogenic function in a manner partly dependent on the repression of RHOB and EGR1 expression in NSCLC cells.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, RhoB loss could induce Rac1-dependent mesenchymal cell invasion in lung cells through the control of PP2A activity, 29 and promote the invasion of human bronchial cells via the activation of AKT1. 42 Furthermore, Mazieres et al 43 also reported that the loss of RhoB expression was induced via epigenetic regulation by histone deacetylation in lung cancer, whereas we found that LSD1 recruited by DUXAP8-mediated histone demethylation also contributed to RHOB loss of expression in NSCLC cells. Interestingly, rescue experiments demonstrated that the pseudogene DUXAP8 exerts oncogenic function in a manner partly dependent on the repression of RHOB and EGR1 expression in NSCLC cells.…”
Section: Discussionmentioning
confidence: 49%
“…Our results showed that miR-21 activates Akt1/mTORC1-mediated cyclin D1 translation by inhibiting Rhob. While Rhob has been shown to inhibit Akt1 (22,23), to our knowledge, it was not previously known that this effect of Rhob results in inhibition of cyclin D1 translation.…”
Section: Discussionmentioning
confidence: 81%
“…Although Rhob had not been implicated in the regulation of cyclin D1 expression, several lines of evidence suggested this possibility. First, Rhob inhibits activating phosphorylation of Akt1 (22,23). Then, activated Akt1 regulates cyclin D1 expression through mTORC1 (24,25).…”
Section: Ref 4)mentioning
confidence: 99%
“…RhoB has previously been implicated in regulating cell adhesion in other cell types. For example, macrophages and fibroblasts from RhoB-null mice have defective adhesion and spreading (Liu et al, 2001;Wheeler and Ridley, 2007), and RhoB depletion inhibits adhesion of human lung epithelial cells (Bousquet et al, 2009). In macrophages, RhoB has been postulated to affect adhesion by affecting surface levels of b-integrins (Wheeler and Ridley, 2007).…”
Section: Rhob Depletion Reduces the Association Of Upar With Integrinsmentioning
confidence: 99%
“…RhoB is often considered a tumour suppressor because its expression is downregulated in some cancers, and this has been linked to its role in stimulating apoptosis (Huang and Prendergast, 2006;Vega and Ridley, 2008;Bousquet et al, 2009). By contrast, RhoB can either stimulate or inhibit cancer migration or invasion depending on the cellular context.…”
Section: Rhob Depletion Reduces the Association Of Upar With Integrinsmentioning
confidence: 99%